Internet access to heterogeneous home area network devices with an OSGi-based residential gateway. (14th January 2008) - Zeadally, Sherali; Kubher, Priya
Home area networks are proliferating rapidly in many residential homes. These networks are being designed to enable remote access and control to services and contents such as music, video, and data. It remains a significant challenge to design a home network that exploits different protocol architectures and standards while allowing interoperability among them. We describe the design and implementation of an architecture (known as a residential gateway) that: enables full interoperability among different technologies by exploiting the Open Service Gateway Initiative (OSGi) technology; provides secure internet access to heterogeneous devices connected to a home area network.